Islamic Law in the Era of Artificial Intelligence: A Systematic Literature Review - Sudirman Sudirman; Sutiah Sutiah; Supriyono Supriyono (Malikussaleh University, Aceh, Indonesia, 2025)
This systematic literature review examines the intersection between Islamic law and artificial intelligence, aiming to identify how Shariah principles address the ethical, legal, and practical challenges posed by emerging AI technologies. The study applies the PRISMA method to analyse 67 peer-reviewed publications from 2010 to 2025 sourced from central databases. The reviewed literature is categorised into five core themes: Shariah-aligned AI ethics, AI personhood and legal responsibility, the integration of AI in Islamic finance and judiciary systems, AI-assisted fatwa issuance and ijtihad, and regulatory gaps in aligning AI with maqasid al-shariah. Findings suggest an increasing scholarly engagement with Islamic jurisprudence as a moral compass for technological governance. However, the research also reveals inconsistencies in theological interpretations and a lack of policy frameworks within Muslim jurisdictions. The review concludes that a cohesive Shariah-based framework for AI ethics is both necessary and timely, and it proposes strategic directions for future research and the development of institutional policy.